STRATEGI PUBLIC RELATIONS DALAM MEMBANGUN BRAND AWARENESS KOMISIDOTCO MELALUI AKUN INSTAGRAM @KOMISIDOTCO - Navisha Zahra, Kayla; Kurniasari, Ni Gusti Ayu Ketut (Jawa Dwipa, 2025)
Komisidotco has become one of the effective social media in increasing brand awareness among the younger generation. The background of this research problem is the importance of social media strategy in building strong relationships with audiences, especially in the 18-35 age segment who are active on platforms such as Instagram. The purpose of this study is to analyze how Komisidotco uses a social media strategy integrated with the SOME theory (Share, Optimize, Manage, Engage) to achieve and increase brand awareness. The method used in this research is descriptive qualitative analysis based on interviews with the Komisidotco team and related literature studies. The results showed that Komisidotco has successfully reached the Brand Recall level and is working towards Top of Mind through the use of casual and humorous language, as well as the utilization of interactive features on Instagram. Authenticity and consistency in communication also contribute to increased audience Engagement and loyalty. In conclusion, Komisidotco's well-planned social media strategy and responsiveness to audience feedback has yielded significant results in increasing brand awareness, making them one of the most remembered and recognized mediums among the younger generation. This strategy not only increases visibility but also builds a strong foundation for long-term growth.